From Mimbar to Media: Da’wah Communication Strategies in Shaping Muslim Communities in the Digital Era - Aditia Esthy Kurniawati; Ujang Dedih Humaedi; Chepiq Aziz; Risma Solehah; Ayi Haedar Saputra; Dindin Saepudin; Dicky Muhammad Siddiq (Islamic Journal of Communication and Public Discourse, 2026)
The rapid development of digital technology has significantly transformed Islamic communication practices, particularly in the context of da’wah. Traditionally conducted through physical platforms, da’wah has increasingly shifted toward digital media, creating new opportunities for interaction and community formation. This study aims to analyze da’wah communication strategies and their role in shaping Muslim communities in the digital era. The research employs a qualitative approach using a literature-based design, involving the systematic review and conceptual analysis of scholarly works related to digital religion and communication. The findings reveal that effective digital da’wah communication is characterized by three main dimensions: message personalization, interactivity, and visual-symbolic representation. These strategies enhance audience engagement, foster emotional connection, and support the formation of collective identity within digital Muslim communities. Furthermore, social media functions not only as a communication channel but also as a dynamic social space where religious meanings and identities are constructed. The study concludes that communication strategies play a crucial role in determining the success of digital da’wah and community cohesion, offering both theoretical contributions to Islamic communication studies and practical implications for developing adaptive da’wah practices in contemporary digital society.